Spin Coating Growth And Characterization Of Indium Nitride Thin Films - Lee, Zhi Yin (2018)
Indium nitride (InN) has received attention of researchers and manufacturing industry because of its unique properties such as narrow energy band gap of 0.7 – 1.0 eV, high electron mobility and low carrier concentration. However, there is relatively few reported studies concerning the growth mechanism of InN, due to the low dissociation temperature of InN and large lattice-mismatch between the film and substrate. The deposition techniques such as metal-organic chemical vapor deposition, molecular beam epitaxy and radio-frequency sputtering have been used to synthesize InN. However, these techniques require an ultrahigh vacuum system, a toxic precursor as well as a relatively expensive and complicated setup. In this work, the growth, characterization, and device application of InN thin films grown on aluminium nitride-template through sol-gel spin coating method followed by nitridation process were studied. The initial phase of this work is to determine the suitable nitridation temperature and duration for the growth of InN thin film. The sol-gel spin coated film (indium nitrate hydrate) was nitrided in ammonia (NH3) ambient at growth temperature ranged 550 – 700 °C for 30 – 60 min. Through these studies, it was found that the optimal conditions for the growth of InN thin film are 600 °C and 45 min, also, it can be determined that the successful growth of InN requires a formation of indium oxide (In2O3). Subsequently, the effects of thermal decomposition of NH3 gas ranging from 700 – 850 °C on InN crystal growth were studied.